TOURISM TERMS IN LINGUISTICS: ANALYSIS, TRANSLATION, AND CULTURAL ADAPTATION - Kuchkarova Gavkhar Abdullayevna (International Scientific and Current Research Conferences, 2025)
This thesis explores tourism terminology from a linguistic perspective, focusing on the structure, semantics, and cultural implications of tourism-related lexical units. The study examines how tourism terms are formed, categorized, and used in English and Uzbek, highlighting the challenges of translating them across languages. It emphasizes the importance of accurate translation and cultural adaptation in international tourism contexts. The thesis also provides strategies for effective terminology management, translation, and professional communication in tourism.